Fixed Points of Generalized F-Suzuki Type Contraction in Complete b-Metric Spaces - Hamed Hamdan Alsulami; Erdal Karapınar; Hossein Piri (Discrete Dynamics in Nature and Society)
We introduce the notion of generalized F-Suzuki type contraction in b-metric spaces and investigate the existence of fixed points of such mappings. The presented results generalize and improve several results of the topics in the literature.